A Review on Regenerative Braking Methodology in Electric Vehicle - Manikandan, J.; Arun, M. (International Journal of Psychosocial Rehabilitation, 2019)
Electric cars will be an interest in the market soon. Today, existing braking technologies are used. This braking technology consumes a lot of energy during braking in the form of heat. Therefore, regenerative braking is the most important method of focusing because it is an energy saving method. Increase the efficiency of electric vehicles by reducing waste of energy. In electric vehicle regenerative braking mode, the kinetic energy of the wheels is converted into electricity and stored in the battery or capacitor. This method has been improved using flywheels, DC-DC converters, supercapacitors. In this paper, various kinds of controllers have been studied to improve the energy saving of electric vehicles.